Medicago truncatula as a model host for studying legume infecting Rhizoctonia solani and identification of a locus affecting resistance to root canker - Anderson, J.; Lichtenzveig, Judith; Oliver, Richard; Singh, K. (Wiley-Blackwell, 2013)
The broad-host-range necrotizing fungal pathogen Rhizoctonia solani is responsible for economically significant diseases to crops as diverse as wheat, maize, barley, canola, sugar beet, potato, soyabean, bean, lupin and alfalfa. Germplasm screens in many of the crop hosts have not identified strong genetic resistance which, together with the lack of effective control, mean the pathogen remains a substantial problem for agriculture in many parts of the world. Following the establishment of a robust inoculation assay, a germplasm collection of the model legume Medicago truncatula was screened with various legume-infecting isolates of R. solani. While some significant differences in susceptibility/resistance were detected between some lines, in the majority of cases M. truncatula was susceptible to R. solani. Comparison of a legume- and cereal-infecting AG8 isolate with a legume-specific AG11 isolate revealed no difference in pathogenicity between the two isolates when infecting M. truncatula. The most significant differences in susceptibility occurred with an AG6 isolate, which caused root canker. This included significant differences between the moderate resistance of the M. truncatula reference genotype A17 and the high susceptibility of line A20. The analysis of a recombinant inbred line population derived from A17 and A20 revealed a single locus contributing to the resistance in A17. Interestingly, the locus only affected the development of post-emergent (late) symptoms, such as necrosis of cotyledons at 11 days after inoculation and root- and above-ground-weights, but not pre-emergent seedling damping off. These findings pave the way for further studies to dissect the genetic and molecular mechanisms of resistance